The Macroeconomics of Dirty Float In A Primary Export Economy: The Case of Peru - Mendoza Bellido, Waldo (2017)
The current Peruvian exchange regime is neither pegged nor free-floating. The Peruvian Central Bank sails against the wind in the exchange market, tending to buy dollars when the exchange rate falls, and tending to sell when the exchange rate rises. It is a dirty float regime.  In this paper we present a simple macroeconomic model where the central bank fixes the interest rate and maintains a dirty floating exchange rate regime, assuming a small, open, and partiallydollarized economy that exports raw materials, faces imperfect capital mobility, and has a structural fiscal deficit limit as a rule for its fiscal policy. The predictions of the model are consistent with the rule of foreign exchange intervention by the Central Bank and the main stylized facts of the Peruvian economy since the decline in the international price of raw materials in late 2011: drastic fall in private investment, decline of GDP growth, rising nominal exchange rate and reduction of international reserves.